Essentials of Investments - Bodie, Zvi.; Kane, Alex.; Marcus, Alan J. (Boston, Mass. : Irwin/McGraw Hill, 1998)
This examination of investment analysis explores the theme of asset allocation, with an emphasis on securities and security analysis and de-emphasizing the technical aspects of portfolio analysis. International examples and topics are also integrated into the text.
Includes index.
Includes bibliographical references (p. 590-593).
rpm 21/09/16
Loans
Keywords: Investments